CONVENTIONAL TO ISLAMIC BANKING: COMPARING STATE-OWNED AND PRIVATE BANK CUSTOMERS - Niken Mahmuda Awali; Rizki Tiara; Bambang Eko Samiono (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The gap between high Islamic financial literacy and low Islamic banking inclusion in Indonesia remains a critical challenge for the industry. This study analyzes the effects of Islamic Financial Literacy (IFL), Perceived Value (PV), and Perceived Fairness (PF) on Switching Intention with Trust as a mediator, comparing state-owned and private bank customers in Jakarta. Using PLS-SEM and Multi-Group Analysis (MGA) on 200 respondents, the results reveal striking pattern differences. For state-owned bank customers, IFL, PV, and PF positively affect Trust and switching intention, with Trust acting as a partial mediator. Conversely, for private bank customers, only PF affects Trust, while PV directly drives switching intention without Trust mediation. MGA results show significant differences in two paths: IFL to Trust (positive for state-owned, negative for private) and Trust to switching intention (significant for state-owned, non-significant for private). These findings contribute to the literature by showing that the switching mechanism is comprehensive and trust-based for the state-owned segment, but pragmatic and value-based for the private segment. Consequently, Islamic banks require differentiated strategies: emphasizing literacy and fairness for state-owned customers, while highlighting functional benefits and social value for private bank customers.